If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + (-10) = -19 2z + -10 = -19 Reorder the terms: -10 + 2z = -19 Solving -10 + 2z = -19 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2z = -19 + 10 Combine like terms: -10 + 10 = 0 0 + 2z = -19 + 10 2z = -19 + 10 Combine like terms: -19 + 10 = -9 2z = -9 Divide each side by '2'. z = -4.5 Simplifying z = -4.5
| y/1-3/4 | | 11y-36+63= | | -5x-x=6 | | -9(5r-3s)= | | x=7(176)-x | | ak^2-11ak+18a= | | 5m-5=-2+5+9m | | X+bc=5 | | 9x^3=10 | | 4x-17+137= | | 2.1=x/2 | | 3(x-4)+8x=19-2(x+3) | | -7/11x=-2 | | 2-(x-1)=5x+9 | | 8k^3-162k= | | 38-g=34 | | 1/3-7=4 | | 4x+45+5x-18= | | -(2s+7)+3(2s+5)-2s= | | -4(4y-7)-y=-3(y-3) | | K-5= | | 8x-6x-4x=12 | | 112=5(6n-2)+2 | | 5m-5=9m+5 | | 12x-14x=12 | | 6y3/2 | | 3.2x=5 | | 9=55-7v | | 22q-(2-4q)=22 | | -6+4(3p-8)=-110 | | 4(3)+1= | | 0.7x=0.6x+50 |